History of Tourism Research in Slovenia - Žarko Lazarević (Mенаџмент у хотелијерству и туризму, 2016)
The aim of the following discussions to describe the basic characteristics of the historical research of tourism in Slovenia. Our purpose is twofold. In the first part we will undertake an analysis of the conceptual foundations of the Slovenian tourism research in the context of the Slovenian economic history. On the other hand we also wish to present the basic developmental aspects of tourism in Slovenia in the context of the wider economic and social development or the context of the consumer society. To put it more succinctly, we wish to present the interpretational framework and basic substantive emphases that the authors use in their presentations of the developmental characteristics of tourism in the 19th and 20th century. Through these optics we will outline the basic developmental orientations on the example of the establishment of the models of tourist consumption practices. Already in the introduction we wish to underline the basic dimension of this discussion as well, as its purpose is to present only the most characteristic points in the research of tourism in Slovenia. However, by no means do we want to draw up a commented bibliography of historiographic articles, discussions or monographs on tourism as an economic or social‑cultural activity in Slovenia. The available space is far too limited for such an endeavour. Thus we only intend to present the most prominent research or publications from the research of the history of tourism in Slovenia from the viewpoint of conceptualisation or from the standpoint of thematisation. We also have to emphasise that this involves a subjective outlook of the author.